Facet Selectivity Guided Assembly of Nanoarchitectures onto Two‐Dimensional Metal–Organic Framework Nanosheets. Issue 32 (30th June 2021) - Li, Zhihao; Gao, Huajian; Shen, Ruichen; Zhang, Caixin; Li, Leisi; Lv, Yawei; Tang, Liming; Du, Yaping; Yuan, Quan
Abstract: Facet‐selective nanostructures in living systems usually exhibit outstanding optical and enzymatic properties, playing important roles in photonics, matter exchange, and biocatalysis. Bioinspired construction of facet‐selective nanostructures offers great opportunities for sophisticated nanomaterials, but remains a formidable task. We have developed a macromolecule‐mediated strategy for the assembly of upconversion nanoparticles (UCNPs)/two‐dimensional metal–organic frameworks (2DMOFs) heterostructures with facet selectivity. Both experimental and theoretical results demonstrate that polyvinylpyrrolidone (PVP) can be utilized as an interface‐selective mediator to further promote the facet‐selective assembly of MOFs onto the surface of UCNPs. The UCNPs/2DMOFs nanostructures with facet selectivity display specific optical properties and show great advantages in anti‐counterfeiting. Our demonstration of UCNPs/2DMOFs provides a vivid example for the controlled fabrication of facet‐selective nanostructures and can promote the development of advanced functional materials for applications in biosensing, energy conversion, and information assurance. Abstract : A facet‐selective nanostructure was constructed by assembly of anisotropic upconversion nanoparticles (UCNPs) with two‐dimensional metal–organic frameworks (2DMOFs) nanosheets. The UCNPs/2DMOFs nanostructures possess facet selectivity and they display specific optical properties that are advantageous in anti‐counterfeiting technology.